International and Regional Competition for the African Coast (Journal of the College of Education for Women, 2019)
This study aimed at analyzing and studying the strategic and geopolitical importance of the Sahel region, which increased the regional competition for the resources of the region, especially the energy resources that have been and continue to be one of the axes of conflict and competition between these forces.The researcher tried to review the competition between the international force, France, the United States of America, China, Algeria and Libya, and the African coast. We note that there is a positive correlation between the severity of the conflict and the intensity of the competition of the major powers to control the countries of the region and the extent of political and economic stability These countries are directly affected by stability and security in the region. The United States is working to limit French influence, while France, in cooperation with China and Libya, is trying to limit American influence and protect its interests in logic. , And this is not to say that the Sahel region was not only an arena for international competition, but was often effective and influential, as the Sahel countries encouraged some parties to enter the arena of competition and objected to the role of other parties, and followed them a foreign policy aimed at economic development And to strengthen political stability in the region. Encouraging these countries to compete was in their interest and attracted foreign investment to their territorie